Conversion of Nitric Oxide into Nitrous Oxide as Triggered by the Polarization of Coordinated NO by Hydrogen Bonding. Issue 17 (22nd March 2016) - Chuang, Chuan‐Hung; Liaw, Wen‐Feng; Hung, Chen‐Hsiung
Abstract: Reduction of the {Co(NO)} 8 cobalt–nitrosyl N‐confused porphyrin (NCP) [Co(CTPP Me )(NO)] (1 ) produced electron‐rich {Co(NO)} 9 [Co(CTPP Me )(NO)][Co(Cp*)2 ] (2 ), which was necessary for NO‐to‐N2 O conversion. Complex2 was NO‐reduction‐silent in neat THF, but was partially activated to a hydrogen‐bonded species2 ⋅⋅⋅MeOH in THF/MeOH (1:1, v/v). This species coupling with2 transformed NO into N2 O, which was fragmented from an [N2 O2 ]‐bridging intermediate. An intense IR peak at 1622 cm −1 was ascribed to ν(NO) in an [N2 O2 ]‐containing intermediate. Time–course ESI(−) mass spectra supported the presence of the dimeric [Co(NCP)]2 (N2 O2 ) intermediate. Five complete NO‐to‐N2 O conversion cycles were possible without significant decay in the amount of N2 O produced. Abstract : Alcohol can H⋅⋅⋅elp : Water, methanol, or ethanol triggered the formation of a [N2 O2 ]‐bridged intermediate from a reduced cobalt–nitrosyl N‐confused porphyrin to enable the conversion of NO into N2 O (see scheme). Hydrogen‐bonding interactions assisted N−N coupling and N−O bond cleavage in the intermediate to generate N2 O.